Analisis Hasil Pertanian Dengan Menggunakan Sistem Informasi Geografis (Studi Kasus : Kota Salatiga) - Fiktor Mijoro (APTIKOM SUMSEL, 2022)
As a country so rich in natural products, the agricultural sector is an activity of utilizing natural resources carried out by humans so that it can produce food, raw materials for agency and industrial businesses, energy and natural balance. Every year the limited agricultural area of the city of Salatiga can be affected by crop yields and agricultural production. Departing from this problem, it is necessary to analyze agricultural products in order to know the increase or decrease in agricultural yields in Salatiga City, the existence of a Geographic Information System (GIS) that can facilitate tools as a decision-making tool by the government or agency. In this research, the methods used are collecting spatial and non-spatial data, analyzing agricultural product data of Salatiga City and digitizing it into a digital map. The result of this research is a digital map that provides information on the mapping of agricultural products in Salatiga City for 4 years starting from 2016-2019.